ANALISIS PELAKSANAAN CUSTOMER RELATIONSHIP MANAGEMENT PADA USAHA KECIL DAN MENENGAH DI KOTA PEKANBARU - Eka Komalasari; Nurmasari Nurmasari (VALUTA, 2020)
This study aims to analyze the implementation of Customer Relationship Management in Small and Medium Enterprises in Pekanbaru City, as well as to see the role of the Office of Cooperatives for Micro and Small and Medium Enterprises in conducting coaching to the Small and Medium Enterprises (SMEs) actors in Pekanbaru. The method used in this research is descriptive qualitative, data collection by interviewing, observing, and documenting with small and medium business actors and the Micro and Small Business Cooperatives Office. The results of research to see the implementation of Customer Relationship Management (CRM) in Small and Medium Enterprises in Pekanbaru City show that small and medium business actors have already run the CRM, even though the CRM is not yet maximized due to the limitations of Human Resources (business actors) in understanding CRM completely. While the results of research to see the role of the Department of Micro, Small and Medium Enterprises in the City of Pekanbaru show that the role of the Department is quite good in carrying out its role to foster existing MSMEs in the city of Pekanbaru, see where the Office is trying to run a Guidance Program for MSMEs even though the budget is insufficient, but activities are still carried out despite training participants are limited, given the efficiency of the existing budget.